End‐stage renal disease and dialysis in HIV‐positive patients: observations from a long‐term cohort study with a follow‐up of 22 years. Issue 3 (20th September 2012) - Bickel, M; Marben, W; Betz, C; Khaykin, P; Stephan, C; Gute, P; Haberl, A; Knecht, G; Wolf, T; Brodt, HR; Geiger, H; Herrmann, E; et al.
<x xml:space="preserve">Abstract</x> Objectives Renal disease is a common and serious complication in HIV‐infected patients. Methods A retrospective cohort analysis for the period 1989–2010 was carried out to determine the prevalence, incidence and risk factors for end‐stage renal disease (ESRD). ESRD was defined as initiation of renal replacement therapy. Three time periods were defined: 1989–1996 [pre‐highly active antiretroviral therapy (HAART)], 1997–2003 (early HAART) and 2004–2010 (late HAART). Results Data for 9198 patients [78.2% male; 88.9% Caucasian; cumulative observation time 68 084 patient‐years (PY)] were analysed. ESRD was newly diagnosed in 35 patients (0.38%). Risk factors for ESRD were Black ethnicity [relative risk (RR) 5.1; 95% confidence interval (CI) 2.3–10.3; P < 0.0001], injecting drug use (IDU) (RR 2.3; 95% CI 1.1–4.6; P = 0.02) and hepatitis C virus (HCV) coinfection (RR 2.2; 95% CI 1.1–4.2; P = 0.03). The incidence of ESRD decreased in Black patients over the three time periods [from 788.8 to 130.5 and 164.1 per 100 000 PY of follow‐up (PYFU), respectively], but increased in Caucasian patients (from 29.9 to 41.0 and 43.4 per 100 000 PYFU, respectively). The prevalence of ESRD increased over time and reached 1.9 per 1000 patients in 2010. Mortality for patients with ESRD decreased nonsignificantly from period 1 to 2 (RR 0.72; P = 0.52), but significantly from period 1 to 3 (RR 0.24; P = 0.006), whereas for patients without ESRD mortality decreased significantly for all comparisons. ESRD was associated with a high overall mortality (RR 9.9; 95% CI 6.3–14.5; P < 0.0001). Conclusion As a result of longer survival, the prevalence of ESRD is increasing but remains associated with a high mortality. The incidence of ESRD declined in Black but not in Caucasian patients. IDU and HCV were identified as additional risk factors for the development of ESRD.